2013
DOI: 10.1093/infdis/jit826
|View full text |Cite
|
Sign up to set email alerts
|

Posttreatment Changes in Cytokines Induced by Schistosoma mansoni Egg and Worm Antigens: Dissociation of Immunity- and Morbidity-Associated Type 2 Responses

Abstract: Background. Human type 2 cytokine responsiveness to schistosome antigens increases after treatment; due either to removal of the immunosuppressive effects of active infection or immunological boosting by antigens released from dying parasites. We determined the responsiveness to Schistosoma mansoni over a 2-year period, when reinfection was restricted by interrupting transmission.Methods. The proinflammatory and type 2 responses of Kenyan schoolchildren were measured before, and 1 year and 2 years posttreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Moreover, using pretreatment worm burden as a proxy for antigen release, the modest increase seen to AscAg was not correlated with burden of Ascaris lumbricoides at pretreatment, nor were responses to nonrelated antigens correlated with baseline worm burden. These findings argue that observed boosted immune responses would not be due to release of antigens from dying worms, which has been shown to account for part of the increase in immune responses after treatment in schistosomiasis (25), but rather be due to the decrease in immune regulation.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, using pretreatment worm burden as a proxy for antigen release, the modest increase seen to AscAg was not correlated with burden of Ascaris lumbricoides at pretreatment, nor were responses to nonrelated antigens correlated with baseline worm burden. These findings argue that observed boosted immune responses would not be due to release of antigens from dying worms, which has been shown to account for part of the increase in immune responses after treatment in schistosomiasis (25), but rather be due to the decrease in immune regulation.…”
Section: Discussionmentioning
confidence: 82%
“…A study conducted in Kenya showed that in schoolchildren infected with Schistosoma mansoni , type 2 cytokine responses including IL‐4, IL‐5, IL‐9 and IL‐13 were significantly increased upon stimulation with egg antigen 1 and 2 years post‐treatment . Another study in Gabon showed that specifically IL‐5, but neither IL‐4 nor IL‐13, was downregulated during an active S. haematobium infection as only IL‐5 responses to worm antigens were increased in subjects who remained free from infection 2 years after helminth clearance, compared to subjects who became reinfected …”
Section: Discussionmentioning
confidence: 99%
“…This enhanced cytokine response can be due to either removal of the immunosuppressive effects of active infection or immunological boosting by antigens released from dying parasites . Although it is possible that treatment boosts the antigen‐specific responses, often also responses to unrelated antigens such as PHA are enhanced by anthelmintic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Infections are distributed in age-dependent patterns; that is, infection intensities increase with age in younger children before falling to lower levels in adulthood [3,4]. Resulting morbidity manifests from CD4 + T cell-mediated granulomatous tissue responses to eggs, not adult worms that are swept into the liver or become trapped in the intestine or urogenital tissues [11]. The cycle is completed by the excretion of viable eggs from the definitive host into these water sources [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases of S. mansoni infections this results in liver fibrosis, portal hypertension and intestinal bleeding. Resulting morbidity manifests from CD4 + T cell-mediated granulomatous tissue responses to eggs, not adult worms that are swept into the liver or become trapped in the intestine or urogenital tissues [11]. Data from murine studies have shown that initially, immune responses start with a Th1 response against the migrating schistosomula and immature adult worms inducing interferon (IFN)-γ.…”
Section: Introductionmentioning
confidence: 99%